Generating EXPRESS Data Models from SBVR: An automated Approach to Generate EXPRESS Data Models from SBVR Specification - Bajwa, Imran Sarwar; Sarwar, Nadeem; Naeem, M. Asif (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
EXPRESS is a standard graphical documentation for data models. It is a helpful buddy to the EXPRESS dialect for showing element and sort definitions, connections and cardinality. This graphical documentation underpins a subset of the EXPRESS dialect. One of the preferences of utilizing EXPRESS over EXPRESS is that the structure of an information model can be exhibited in a more reasonable way. In software engineering the graphical representation of the software structure is very necessary because understanding of coding is very difficult. Semantic Business Vocabulary Rules (SBVR) specifications many authors have done model to model transformation. SBVR2EXPRESS is also possible. In this study we propose an EXPRESS data model using Natural language. That model manually implements on two case studies and generate the EXPRESS diagram using SBVR rules. That diagram full fills the all software requirement of the Software engineers. Model representation is very helpful to develop large scale of systems like, Aerospace, medical science and other industries where the representation of system working is very important. This work is very helpful to the Data manger and IT managers to represent their organization structure.